The Impact of Corporate Governance and Capital Structure on the Financial Performance of Public Companies: Dampak Tata Kelola dan Struktur Modal terhadap Kinerja Keuangan Perusahaan BUMN yang Terdaftar di BEI - Islamiyati, Dian; Cahyono, Ari Nugroho; Putri, Nia Rifanda (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The aim of this research is to examine the impact of governance and capital structure on company performance. The population of this research is state-owned companies listed on the Indonesian Stock Exchange during 2019-2022. The sample for this research consisted of 76 samples using the purposive sampling method. The results of hypothesis testing with Smart PLS show that corporate governance variables and capital structure variables have an effect on company performance.